Coherent neutrino scattering with low temperature bolometers at Chooz reactor complex. (21st August 2017) - Billard, J; Carr, R; Dawson, J; Figueroa-Feliciano, E; Formaggio, J A; Gascon, J; Heine, S T; Jesus, M De; Johnston, J; Lasserre, T; Leder, A; Palladino, K J; et al.
Abstract: We present the potential sensitivity of a future recoil detector for a first detection of the process of coherent elastic neutrino nucleus scattering (CE ν NS). We use the Chooz reactor complex in France as our luminous source of reactor neutrinos. Leveraging the ability to cleanly separate the rate correlated with the reactor thermal power against (uncorrelated) backgrounds, we show that a 10 kg cryogenic bolometric array with 100 eV threshold should be able to extract a CE ν NS signal within one year of running.